MECHANISM ANALYSIS OF 2006 YOGYAKARTA EARTHQUAKE, USING COULOMB STRESS CHANGE - Budiman, Rizky
in Yogyakarta, Indonesia. The source of the event is still debatable. Many experts believe the event was caused by reactivation of the Opak Fault which has a left-lateral type movement. But, the others say different, they assume reverse slip movement was the event source. From the two opinions,, the writer tries to model the two possibilities of event source 2006. First is based on focal mechanism from NIED (National Research Institute for Earth Science and Disaster) Japan which indicated the event occurred with an oblique reverse slip. This model explains that active and old Opak fault is a flower structure (strike-slip) type. Second is based on NEIC (National Earthquake Information Center) US which indicated that the event was caused by a pure strike-slip fault (active Opak fault). The May 26th earthquake triggered many aftershock events around the old Opak fault. The aftershock events on 3-6 June 2006 were located around 5 km east of Opak fault. It has a trendline of N45°E and lies parallel with the Opak fault. This pattern is interpreted as a fault which is cause of aftershocks event. The writer uses Coulomb Stress change to determine which type of source model fit the aftershocks pattern.The result is the first model, which is reverse fault model, can better explain the mainshock and aftershocks of 2006 Yogyakarta earthquake. This is supported by suitability of of the stress change pattern with the aftershocks distribution and the earthquake damage area. The faults, which produce the earthquakes in the study area, have a high slip tendency value and positive Coulomb stress value.